EKSPERIMENTASI MODEL PEMBELAJARAN MISSOURI MATHEMATICS PROJECT (MMP) DAN MODEL PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) DISERTAI ASSESSMENT FOR LEARNING MELALUI TEMAN SEJAWAT DITINJAU DARI KEMANDIRIAN BELAJAR SISWA KELAS X SMA DI KABUPATEN - Nugroho, Purna Bayu; Budiyono, Budiyono; Subanti, Sri (Jurnal Pembelajaran Matematika, 2014)
Abstract. The purposes of this study were to determine: (1) which has better learning achievement, students are given MMP learning model with AfL through peers, STAD with the AfL through peers, or students who were given direct learning model, (2) which has better learning achievement, students with learning independence of high, moderate or low, (3) on each learning model, which one has the better learning achievement, students with learning independence of high, moderate or low, (4) in each learning independence category, which has better learning achievement, students are given MMP learning model with AfL through peers, STAD with AfL through peers or students who given direct learning model. This study was a quasi-experimental study with a 3 x 3 factorial design. The study populations were all of grade X students of Senior High School in Bantul. Sampling was done by stratified cluster random sampling. The samples in this study amounted to 214 students with the details of 72 students for experiment 1 and 70 for experiments 2 and 72 for the control class. The data collected instrument used mathematics achievement tests and a questionnaire of studentâs learning independence. Based on the hypothesis testing, it can be concluded as follows. (1) Studentsâ learning achievement treated by MMP learning model with the AfL better than students treated by STAD models with AfL and direct learning model. In addition, studentsâ learning achievement treated by STAD model with AfL through peers better than students treated by direct learning model. (2) Studentsâ learning achievement which has high learning independence better than students who have moderate and low independence. In addition, students who have moderate learning independence better than students who have low learning independence. (3) In the MMP learning model with the AfL through peers, STAD with AfL through peers and direct learning model, the studentsâ learning achievement who have high learning independence better than moderate and low learning independence, in addition the studentsâ learning achievement who have moderate learning independence better than students who have low learning independence. (4) In the learning independence category of high, moderate and low, the studentsâ learning achievement treated by MMP with the AfL through peers better than students treated by STAD with AfL through peers and direct learning model. In addition, studentsâ learning achievement treated by STAD with AFL through peers better than students treated by direct learning model.Keywords: Missouri Mathematics Project (MMP), Student Teams Achievement Divisions (STAD), Assessment for Learning (AfL), Peers, Studentâs Learning Independence